The development of the Senior Golfers Movement Assessment (SGMA) and its associated intra- and inter-rater reliability - Martin, S.; Evans, V.; Salmon, J.; Dixon, S.; Williams, G. K. (International Journal of Golf Science, 2025)
Senior golfers are susceptible to declines in strength, flexibility, and coordination, which can impact performance and increase injury risk, making appropriate monitoring essential (Lindsay et al., 2000). This study introduces the Senior Golfers Movement Assessment (SGMA) and evaluates its intra- and inter-rater reliability. The SGMA consists of ten exercises for a 100-point composite score. Nineteen amateur senior golfers (age 67.16 ±6.44 years, handicap 20.3 ±6.4) were videoed performing the SGMA. Three raters independently assessed and scored each participant, with one rater reassessing after four weeks. Intraclass correlation coefficient (ICC) and standard error of measurement (SEM) values were calculated for composite scores, and weighted kappa values (Kw) were calculated for individual exercises. Reliability of the composite score was ICC=0.99, SEM=0.28 (intra-rater) and ICC=0.97, SEM=0.45 (inter-rater). Individual sub-test reliability ranged from Kw=0.02 to 0.78 (intra-rater) and Kw=-0.02 to 0.44 (inter-rater). While the SGMA demonstrates high reliability in the composite score, variation in reliability of individual exercise scores indicates that the criteria for these sub-tests require further refinement to enhance consistency across raters and reduce time to administer.